The bride next door - Ramsay, Hope (Ramsay, Hope. Chapel of Love series., 2018)
Courtney Wallace loves her job as a wedding planner, but she's almost given up on her own happily-ever-after. She certainly doesn't it expect to find it with Matthew Lyndon, the hotshot lawyer she overhears taking a bet to seduce her. She's not amused by the challenge, but she decides to play along--after all, what better way to beat him at his own game? Matt never intended to take the bet seriously. And moving next door wasn't part of his strategy to win-it was just a happy coincidence-but the more he gets to know Courtney, the more intrigued he becomes. When fun and games turn into something real, will these two decide they're in it to win it?